Meningkatkan Aktivitas dan Hasil Belajar Siswa Pada Materi Pentingnya Hidup Rukun di Masyarakat Melalui Pendekatan Kontekstual Di Kelas II SDN 53/IX Kenali Kecil - Najmiati Najmiati (Peneliti.net, 2021)
This study aims to improve student learning outcomes in the Civics subject matter of Norms in the Community through a Contextual Approach to Class II Students of SDN 53/IX Kenali Kecil. The research method used is Classroom Action Research (CAR), which is research conducted by classroom teachers where they teach by emphasizing improving practices and processes on material norms in society so that later student learning outcomes increase. The research subjects were all second grade students of SDN 53/IX Kenali Kecil, totaling 20 students. The implementation of 3 cycles, each cycle is carried out 3 x meetings, each cycle is designed in 4 (four) activities, namely: (1) Planning, (2) Action Implementation, (3) Observation and Evaluation, (4) Analysis and Reflection. Date on learning mastery is taken with a test instrument. Date analysis generally uses technical percentages. The results showed that the first cycle of students who completed 54.3%, in the second cycle students who completed 62.6% and in the third cycle students who completed 87.5%. Thus, it can be concluded that student learning is complete in cycle III, which means that the Contextual Approach can improve student activities and learning outcomes on the material The Importance of Living in harmony in the Community in Class II SDN 53/IX Kenali Kecil